Samuel Beckett and the meaning of being : Study in ontological parable - "Butler, John." (London, 1984)
Do we take Beckett seriously enough? this study starts from assumption that we do not, and that this arises from an unwillingness to face up to the central philosophical issues implicit in his work. critics agree that there is some sort or connection between Beckett and numerous thinkers. Philosophical and religious, but these connections have been inadequately explored.
Keywords: Ontology